Performance analysis of adaptive controllers on chaotic parameter modulation and variant channel gain - Türk, M; Ata, F (St Petersburg State Polytechnic Univ, 2002)
In this study, effects of different adaptive controllers used in chaotic secure communication is numerically investigated. Effects of adaptive controllers on channel noise and chaotic modulation are numerically examined. Furthermore, effective parameters of adaptive controllers on recovered signal quality are investigated. Numerical results obtained for different controllers are compared.
1st IEEE International Conference on Circuits and Systems for Communications -- JUN 26-28, 2002 -- ST PETERSBURG, RUSSIA
Keywords: chaos; chaos modulation; Chua's circuit; adaptive control; controllers